2018
DOI: 10.2298/pim1817061g
|View full text |Cite
|
Sign up to set email alerts
|

Flat double rotational surfaces in Euclidean and Lorentz-Minkowski 4-space

Abstract: A new type of surfaces in 4-dimensional Euclidean and Lorentz-Minkowski space is constructed by performing two simultaneous rotations on a planar curve. In analogy with rotational surfaces, the resulting surfaces are called double rotational surfaces. Classification theorems of flat double rotational surfaces are proved. These classifications contain amongst other cones over 4-dimensional Clelia curves. As a side product these new kinds of curves in 4-space are defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…They also showed that there exists no minimal (regular) twisted surface in Euclidean or in Minkowski 3-space when excluding the surfaces of revolution. In another study by the same authors, the curvature properties of twisted surfaces with null rotation axis in Minkowski 3-space were studied [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also showed that there exists no minimal (regular) twisted surface in Euclidean or in Minkowski 3-space when excluding the surfaces of revolution. In another study by the same authors, the curvature properties of twisted surfaces with null rotation axis in Minkowski 3-space were studied [6].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the generalization of rotational surfaces and their related properties from 3-dimensional Euclidean space to 4-dimensional space [13], Twisted surfaces are defined in 4-dimensional Euclidean space and 4dimensional Lorentz space and their related properties are studied in detail [6].…”
Section: Introductionmentioning
confidence: 99%
“…In [5], a brief description of the hyperbolic and elliptic rotational surfaces is defined using a curve and matrices in 4-dimensional semi-Euclidean space and different types of rotational matrices which are the subgroups of M by rotating a selected axis in E 4 are given by the authors. In [8], A new type of surfaces in Euclidean and Lorentz-Minkowski 4-space are constructed by performing two simultaneous rotations on a planar curve by the authors. Also, the classification theorems of flat double rotational surfaces are proved by the authors.…”
Section: Introductionmentioning
confidence: 99%
“…In [5], a brief description of the hyperbolic and elliptic rotational surfaces is defined using a curve and matrices in semi-Euclidean 4-space and different types of rotational matrices which are the subgroups of M by rotating the axis in E 4 are given by the authors. In [8], A new type of surfaces in Euclidean and Lorentz-Minkowski 4-space is constructed by performing two simultaneous rotations on a planar curve by the authors. Also, classification theorems of flat double rotational surfaces are proved by the authors.…”
Section: Introductionmentioning
confidence: 99%